Circadian Cyp3a11 metabolism contributes to chronotoxicity of hypaconitine in mice. (1st August 2019) - Lin, Yanke; Zhou, Ziyue; Yang, Zemin; Gao, Lu; Wang, Shuai; Yu, Pei; Wu, Baojian
Abstract: Hypaconitine is an active and highly toxic constituent derived from Aconitum species. Here we aimed to determine the chronotoxicity of hypaconitine in mice, and to investigate a potential role of metabolism in hypaconitine chronotoxicity. Cardiac toxicity was assessed by measuring CK (creatine kinase) and LDH (lactate dehydrogenase) levels after hypaconitine administration to wild-type and Bmal1 −/− (a clock disrupted model) mice at different times of day. The mRNA and protein levels of Cyp3a11 in mouse livers were determined by qPCR and western blotting, respectively. In vitro metabolism was assessed using liver microsomes. Pharmacokinetic study of hypaconitine was performed with wild-type mice. We observed injection time-dependent toxicity (i.e., a more severe toxicity during the light phase than the dark phase) for hypaconitine in mice. The chronotoxicity was attributed to a difference in systemic exposure of hypaconitine caused by time of day-dependent metabolism. Furthermore, circadian metabolism of hypaconitine was accounted for by the diurnal expression of Cyp3a11, a major enzyme for hypaconitine detoxification in the liver. Moreover, Bmal1 ablation in mice abolished the daily rhythm of Cyp3a11 expression and abrogated the time-dependency of hypaconitine toxicity. In conclusion, circadian Cyp3a11 metabolism contributed to chronotoxicity of hypaconitine in mice. This metabolism-based chronotoxicity would facilitate the formulation of best timing for drug administration. Highlights: Hypaconitine exhibits dosing time-dependent toxicity with a more severe toxicity in the light phase than in the dark phase. Hepatic Cyp3a11 expression is diurnal, accounting for circadian metabolism and chronotoxicity of hypaconitine. Bmal1 regulates diurnal rhythm of Cyp3a11 expression and chronotoxicity of hypaconitine.